IInhibition of heterocyclic amines in beef patties by spices - Nimkar, Manasi (Kansas State University, 2013)
Heterocyclic amines (HCAs) formed during cooking of meats at high temperatures are suspected cancer causing compounds and efforts have been made to reduce their levels. Spices possessing high levels of antioxidants have been shown to inhibit these compounds when incorporated prior to cooking. Seven spices, black pepper, rosemary, turmeric, thyme, cinnamon, ginger and oregano were analyzed for their antioxidant capacity using three different assays. These spices were individually added at 0.25% to beef patties fried at 400 °F for 5 min per side to evaluate their effect on HCA inhibition. Black pepper was emphasized in this study by studying the effect of addition at different concentrations (0.25, 0.50, 1.00 %) on HCA reduction. It was found that patties treated with black pepper individually, as well in combination with other spices, greatly decreased the formation of HCAs. Black pepper at 0.25% level showed the highest inhibition of PhIP levels (85%). The spices were shown to have high levels of free radical scavenging activity as measured by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Overall, black pepper had significantly lower DPPH scavenging activity but still showed high HCA inhibition. All the spices individually inhibited HCA by 55-82%. Black pepper in combination with turmeric was the best combination, showing a 94.74% inhibition of HCA formation.
Keywords: Inhibition of heterocyclic amines; Food Science (0359)